Diagnosis of patients with heart failure with preserved ejection fraction in primary care: cohort study - Forsyth, F; Brimicombe, J; Cheriyan, J; Edwards, D; Hobbs, FDR; Jalaludeen, N; Mant, J; Pilling, M; Schiff, R; Taylor, CJ; Zaman, MJ; Deaton, C (Wiley, 2021)
Aims Heart failure with preserved ejection fraction (HFpEF) accounts for half of all heart failure (HF), but low awareness and diagnostic challenges hinder identification in primary care. Our aims were to evaluate the recruitment and diagnostic strategy in the Optimise HFpEF cohort and compare with recent recommendations for diagnosing HFpEF.